Shielding characteristics of water - Levchenko, A.A.; Likhter, A.M.; Khramov, D.A.; Gryaznova, V.A.; Shikin, V.B. (Физика низких температур, 2015)
In this article we demonstrate that a relatively small density of intrinsic ions in pure water has a significant
impact on the development of the instability of the liquid–vapor boundary in an external electric field perpendicular
to the interface. Dielectric breakdown scenario (Shliomis model) is shunted by alternative metal scenario
(Frenkel model). Experimentally we observed the formation of a positively charged layer beneath the
surface in weak perpendicular electrical fields. In strong electrical fields surface of water loses its stability
and charges pass through the interface. Surface discharge process is periodic with a characteristic time of the
order of tens seconds.